Examining information-seeking behavior in genetic testing for cancer predisposition: A qualitative interview study. Issue 2 (February 2021) - Zimmermann, Bettina M.; Fanderl, Julia; Koné, Insa; Rabaglio, Manuela; Bürki, Nicole; Shaw, David; Elger, Bernice
Highlights: Emotions and attitudes affect information-seeking for genetic testing. Patient-counselor relationships influence information-seeking. Prior knowledge can motivate or hinder information-seeking. Trustworthy and clear information beyond genetic counseling is difficult to find. All healthcare professionals need genetics education. Abstract: Objective: This study aims to assess information needs and information sources and seeks to illustrate what at-risk individuals consider motivators of and barriers to information-seeking before and after genetic testing for cancer predisposition. Methods: Semi-structured interviews with people seeking genetic counseling in Switzerland were analyzed qualitatively using thematic analysis. Wilson's model of information behavior was the theoretical framework. Results: We identified four themes that illustrate motivators of and barriers to information-seeking: attitudes and emotions; knowledge; social environment; and demographic factors. We also elucidated information needs and collected participants' information sources. Conclusion: This study£s empirical approach helps healthcare professionals to understand their patients' behaviors and wishes concerning information-seeking more concretely than theoretical models alone. The study also identifies information gaps, especially outside the genetic counseling setting. Practice implications: Genetic counselors and other healthcare professionals need to purposefully assist patients in finding trustworthy and accessible information. Healthcare professionals in all disciplines need to be educated about predictive genetic testing.